2013
DOI: 10.1176/appi.ps.004532012
|View full text |Cite
|
Sign up to set email alerts
|

Does the Redesign of a Psychiatric Inpatient Unit Change the Treatment Process and Outcomes?

Abstract: Efforts to improve the inpatient environment by supporting patient autonomy, peer support, and practical skill development may be expected to meet with improved outcomes, at least for quality of life and satisfaction with treatment. These findings are consistent with patient-centered design as well as with broader perspectives on recovery-oriented services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…17,24,31,33 Notably, in the Canadian study, patients on the home-like ward showed lower improvements in function compared with the control ward, and this negative effect was attributed to staff changes post-intervention. 31 One study reporting a significant drop in violence post-intervention was located in a ward with very low incidence of violence. 26 It is clearly possible to collect large data-sets, but often other factors are not taken into account.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…17,24,31,33 Notably, in the Canadian study, patients on the home-like ward showed lower improvements in function compared with the control ward, and this negative effect was attributed to staff changes post-intervention. 31 One study reporting a significant drop in violence post-intervention was located in a ward with very low incidence of violence. 26 It is clearly possible to collect large data-sets, but often other factors are not taken into account.…”
Section: Discussionmentioning
confidence: 98%
“…23,30 But reports of positive behavioural change were by no means universal: notably, some studies found no significant behavioural effects, yet reported an increase in treatment satisfaction after the intervention. 25,31 In one case, some negative behavioural effects were observed post-intervention (increase in sleeping and watching television). 20 The findings on conflicting perceptions between patient and staff that are supported by both quantitative and qualitative studies also have strong policy implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The literature is unclear regarding the effects of design, comfort, environment, and structure of psychiatric units on clinical outcomes. Some studies have shown an improvement in the perception of the environment, 34,35 changes in social behavior 36 and treatment satisfaction and quality of life 35 in wards that redesigned their facilities. However, this remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…health-care point of view (see, for instance, [52] for a recent study on how the ward atmosphere appears to mediate the associations between the physical and therapeutic characteristics of an inpatient ward and patient outcomes).…”
Section: Introductionmentioning
confidence: 99%